Clinical, biological and genetic analysis of prepubertal isolated ovarian cyst in 11 girls. - Raja Brauner (Public Library of Science (PLoS), 2010)
Background The cause of isolated gonadotropin-independent precocious puberty (PP) with an ovarian cyst is unknown in the majority of cases. Here, we describe 11 new cases of peripheral PP and, based on phenotypes observed in mouse models, we tested the hypothesis that mutations in the GNAS1, NR5A1, LHCGR, FSHR, NR5A1, StAR, DMRT4 and NOBOX may be associated with this phenotype. Methodology/principal findings 11 girls with gonadotropin-independent PP were included in this study. Three girls were seen for a history of prenatal ovarian cyst, 6 girls for breast development, and 2 girls for vaginal bleeding. With one exception, all girls were seen before 8 years of age. In 8 cases, an ovarian cyst was detected, and in one case, suspected. One other case has polycystic ovaries, and the remaining case was referred for vaginal bleeding. Four patients had a familial history of ovarian anomalies and/or infertility. Mutations in the coding sequences of the candidate genes GNAS1, NR5A1, LHCGR, FSHR, NR5A1, StAR, DMRT4 and NOBOX were not observed. Conclusions/significance Ovarian PP shows markedly different clinical features from central PP. Our data suggest that mutations in the GNAS1, NR5A1, LHCGR, FSHR StAR, DMRT4 and NOBOX genes are not responsible for ovarian PP. Further research, including the identification of familial cases, is needed to understand the etiology of ovarian PP.